Bioactive biodegradable polycitrate nanoclusters enhances the myoblast differentiation and in vivo skeletal muscle regeneration via p38 MAPK signaling pathway - Yi Guo; Min Wang; Juan Ge; Wen Niu; Mi Chen; Wei Cheng; Bo Lei (Bioactive Materials, 2020)
Complete skeletal muscle repair and regeneration due to severe large injury or disease is still a challenge. Biochemical cues are critical to control myoblast cell function and can be utilized to develop smart biomaterials for skeletal muscle engineering. Citric acid-based biodegradable polymers have received much attention on tissue engineering, however, their regulation on myoblast cell differentiation and mechanism was few investigated. Here, we find that citrate-based polycitrate-polyethylene glycol-polyethylenimine (POCG-PEI600) nanoclusters can significantly enhance the in vitro myoblast proliferation by probably reinforcing the mitochondrial number, promote the myotube formation and full-thickness skeletal muscle regeneration in vivo by activating the myogenic biomarker genes expression of Myod and Mhc. POCG-PEI600 nanoclusters could also promote the phosphorylation of p38 in MAP kinases (MAPK) signaling pathway, which led to the promotion of the myoblast differentiation. The in vivo skeletal muscle loss rat model also confirmed that POCG-PEI600 nanoclusters could significantly improve the angiogenesis, myofibers formation and complete skeletal muscle regeneration. POCG-PEI600 nanocluster could be also biodegraded into small molecules and eliminated in vivo, suggesting their high biocompatibility and biosafety. This study could provide a bioactive biomaterial-based strategy to repair and regenerate skeletal muscle tissue.